Parental Reports of Preschoolers' Lexical and Syntactic Development: Validation of the CDI-III for European Portuguese - Cadime, Irene; Santos, Ana Lúcia; Ribeiro, Iolanda; Viana, Fernanda Leopoldina (Frontiers in Psychology, 2021)
The present study presents the validation analysis of the European Portuguese version of the MacArthur-Bates Communicative Development Inventory III (CDI-III-PT). The CDI-III-PT is a parental report measure allowing to assess expressive vocabulary and the syntactic abilities of children aged 2;6 to 4;0. In this study, we present a version comprising a lexical subscale which follows the Swedish adaptation and an original syntactic subscale allowing to include language-specific structures. The reports of 739 children were collected; in addition, a standardized measure of language was also administered to a sub-sample of these children and the reports of preschool teachers were collected for another sub-sample. The results indicate a high internal consistency of the lexical and the syntactic subscales. As for sociodemographic variables often found to be predictors of language development, as measured by this type of instruments, the results indicate that age and maternal education are significant predictors of the scores, and that first-born children attain higher scores in vocabulary than later born children, but no significant gender differences were found. The scores of the CDI-III-PT are positively correlated with the ones obtained in the standardized language measure, thus supporting their validity. A high agreement between the reports of parents and teachers was also found. These findings indicate that the CDI-III-PT has adequate psychometric properties and that it can be a useful tool for research and clinical practice. The age-based norms that are now provided can be used to evaluate whether a child is performing poorly compared to their peers.